Abortion at the edges: Politics, practices, performances. (May 2020) - Baird, Barbara; Millar, Erica
Abstract: This article provides a brief overview of the state of discourse, politics and provision of abortion in the Anglophone West, including developments in the wake of the COVID-19 pandemic. It then surveys three promising directions for feminist abortion scholarship. The first is work inspired by the Reproductive Justice Movement, that points to the intersectional axes of inequality that shape abortion discourse and position us in relation to reproductive choice and access issues. The second is work that examines the particularity of the constitution of the aborting body, reflecting the particularity of the pregnant body. This is a specific body, with a specific history; abortion discourse draws from and makes a significant contribution to the meaning and lived experience of this body. The third area of scholarship we highlight is that which seeks to amplify the meaning of abortion as a social good. Much abortion scholarship is attuned to a critique of negative aspects of abortion—from its representation in popular culture to restrictive law and access issues. This is critical work but/and the performative nature of abortion scholarship, like all discourse, means that it can amplify the association of negativity with abortion. The article concludes by introducing the articles contained in the special section of Women's Studies International Forum, 'Abortion at the edges: Politics, practices, performances'.